1988
DOI: 10.1161/01.hyp.11.6.627
|View full text |Cite
|
Sign up to set email alerts
|

Altered biochemical and functional responses in aorta from hypertensive rats.

Abstract: SUMMARY Factors that lead to supersensitivity of vascular smooth muscle to norepinephrine during aldosterone-salt-induced hypertension in rats appear to reside beyond ligand-a-adrenergic receptor binding, which we have shown previously to be normal. The objective of this study was to determine whether significant shifts occur in the coupling between receptors and the production of putative second messengers. Measures of [ 3 H]mjo-inositol phosphates in aorta (endothelium removed) exhibited a concentration-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…7 Hyperreactivity of vascular smooth muscle to adrenergic stimulation has been suggested as a major cause for the increase and maintenance of BP in animal models such as spontaneously hypertensive rats (SHR) and deoxycorticosterone acetate (DOCA)-salt hypertensive rats. 3,6,8,9 Catecholamines cause vascular smooth muscle contraction by activating ␣ 1 -adrenergic receptors (␣ 1 -ARs), and drugs that block ␣ 1 -ARs lead to a fall in peripheral vascular resistance and in venous return to the heart and in BP. Three subtypes of ␣ 1 -AR (␣ 1A , ␣ 1B , and ␣ 1D ) have been isolated and shown to share a high degree of structural similarity (50% to 60% amino acid identity).…”
mentioning
confidence: 99%
“…7 Hyperreactivity of vascular smooth muscle to adrenergic stimulation has been suggested as a major cause for the increase and maintenance of BP in animal models such as spontaneously hypertensive rats (SHR) and deoxycorticosterone acetate (DOCA)-salt hypertensive rats. 3,6,8,9 Catecholamines cause vascular smooth muscle contraction by activating ␣ 1 -adrenergic receptors (␣ 1 -ARs), and drugs that block ␣ 1 -ARs lead to a fall in peripheral vascular resistance and in venous return to the heart and in BP. Three subtypes of ␣ 1 -AR (␣ 1A , ␣ 1B , and ␣ 1D ) have been isolated and shown to share a high degree of structural similarity (50% to 60% amino acid identity).…”
mentioning
confidence: 99%
“…In the present experiments, mean pD 2 and pK t values for arteries from sham rats were within the 95% confidence band for the theoretically expected relation, suggesting that the mean pD 2 value approximates the value for pK t . In contrast, pD 2 and pK, values in arteries from DOCA hypertensive rats fell outside the derived 95% confidence band, indicating that factors other than receptor affinity are involved in the determination of sensitivity in these vessels. However, this result is also consistent with an increase in the number of receptors.…”
Section: 00mentioning
confidence: 66%
“…2 It has been suggested that inositol 1,4,5-trisphosphate-mediated mobilization of intracellular calcium is an important step in the activation of contraction in vascular smooth muscle. 15 Based on measures of 45 Ca 2+ efflux, this study demonstrates that norepinephrine-induced release of intracellular calcium is increased in mesenteric arteries from DOCA hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortae from aldosterone-Others have shown an ai-adrenoceptor activation of phospholipase C (PLC) in vascular smooth muscle in rat aorta [6][7][8]. In subsequent studies of phosphatidic acid production, we have demonstrated a leftward shift in the norepinephrine concentration-response curve in AHR compared with CSR [9], These data imply a possible alter ation in norepinephrine-stimulated PLC activation in AHR resulting in increases of diacylglycérol (DAG) and/or subsequent DAG kinase activity [9], Another product of the PLC pathway is arachidonic acid which is released from DAG by the enzyme DAG lipase [10]. Ara chidonic acid is also released from other phospholipids by phospholipase Ai (PLAi).…”
Section: Introductionmentioning
confidence: 88%